Pertumbuhan Laba Pada Lembaga Perkreditan Desa - Sujana, Ketut; Suardhika, I Made Sadha; Dwirandra, A.A.N.B. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 2 (2018), 2018)
Village Credit Institution (LPD) operates as banking and the performance measurement (for the health level)  is like a bank, although LPD is not a bank. The positive profit growth reflects the LPD will be able to grow  in its operations. This research has objectives to determine the effect of Capital, Asset, Earning, Liquidity  (CAEL) and Non Performing Loan (NPL) to affect the profit growth in LPD. Empirical studies were conducted  on LPDs in Badung-Bali Regency in the period of 2013-2015 with the sample amount of 53 LPDs. The data  used in this research is secondary data, which was obtained from Lembaga Pemberdayaan Lembaga  Perkreditan Desa Kabupaten (LPLPDK) Badung and some were obtained from LPD directly. The analysis  technique used is multiple linear regressions. The result in this research showed that BOPO has negatif effect  to the profit growth. Meanwhile, CAR, KAP, PPAP, ROA, LACLR, LDR, and NPL do not significantly affect the  profit growth. Keywords:  Village Credit Institution (LPD), CAEL, NPL, profit growth